"I am not getting your money": boundary making and identities in immigrant economies in Hong Kong. Issue 2 (6th August 2019) - Kwok, K.
Abstract : Purpose: This paper aims to explore how immigrant small business owners construct entrepreneurial identities by deploying strategies of boundary making in Hong Kong. Design/methodology/approach: Conceptually, it departs from the theoretical discussions of immigrant economy and ethnic boundary making. The analyzes are based on qualitative data collected from in-depth interviews and participant observation primarily in the South Asian immigrant economies in Hong Kong in the period 2014-2017. Findings: Four strategies of boundary work including blurring boundaries, inversion of boundaries, personal repositioning and reconfirming of boundaries are identified. They bring to light that small immigrant entrepreneurs in Hong Kong still encounter considerable obstacles in the process of social integration. Boundary work serves as strategies to release sentiments that would symbolically bring them closer to the mainstream society. Following the "city as context" framework (Brettell, 1999 ; Foner, 2007 ), this paper argues that the various boundary making strategies have been shaped by the legacies of racism, neoliberal governance of integration and urban work ethos highlighting problems and individual responsibilities in Hong Kong. Originality/value: This paper contributes to the literature of the immigrant economy and social integration. First, it sheds light on the role of symbolic meanings and non-economic gains of immigrant entrepreneurship in social integration. Second, it illuminates our understanding that immigrant economy can provide a channel for advancing and weakening social status, thus reminding us not to assume the path of social integration as a straightforward and positive one.